2005
DOI: 10.1093/humrep/deh667
|View full text |Cite
|
Sign up to set email alerts
|

Low oocyte mitochondrial DNA content in ovarian insufficiency

Abstract: Our results suggest that low mtDNA content is associated with the impaired oocyte quality observed in ovarian insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
199
3
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(220 citation statements)
references
References 31 publications
7
199
3
3
Order By: Relevance
“…Recently, it was reported that there is a very short period of mtDNA synthesis from the 1-cell to 2-cell stage, which can be affected by environmental stress in mice (McConnell & Petrie 2004). Further, May-Panloup et al (2005a, 2005b) observed a decrease of mtDNA copy number during 2-cell to morula stage and the following increase at blastocyst stage in in vitro produced bovine embryo. Overall, mtDNA copy number is expressed as a result of balance between the synthesis and the degradation of mtDNA and in vitro production procedure including IVC could impair the balance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, it was reported that there is a very short period of mtDNA synthesis from the 1-cell to 2-cell stage, which can be affected by environmental stress in mice (McConnell & Petrie 2004). Further, May-Panloup et al (2005a, 2005b) observed a decrease of mtDNA copy number during 2-cell to morula stage and the following increase at blastocyst stage in in vitro produced bovine embryo. Overall, mtDNA copy number is expressed as a result of balance between the synthesis and the degradation of mtDNA and in vitro production procedure including IVC could impair the balance.…”
Section: Discussionmentioning
confidence: 96%
“…The mitochondrial copy number has been reported in oocytes from mice (Piko & Taylor 1987, bovines , pigs (El Shourbagy et al 2006) and humans (Steuerwald et al 2000, Reynier et al 2001, May-Panloup et al 2005a) but, to date, there is no report of the mDNA copy number in rat oocytes. Pioneering studies by Piko & Taylor (1987) showed that the quantity of mtDNA remains stable throughout early development in mice, suggesting an absence of mtDNA replication during preimplantation; however, it has been suggested that there is a very short period of mtDNA synthesis immediately after fertilization in mice, which can be affected by environmental stress (McConnell & Petrie 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Equally impressive, however, is the substantial accumulation of mitochondrial (mt) DNA (Dumollard et al 2007, St John et al 2010, Van Blerkom 2010. Although there is some variability among reports, particularly in humans, current data indicate that a mature fertilizable mammalian oocyte harbors 150 000-250 000 copies of mtDNA depending on the species (mouse (Piko & Taylor 1987, Cao et al 2007, human (Steuerwald et al 2000, Reynier et al 2001, Barritt et al 2002, May-Panloup et al 2005, Santos et al 2006, Zeng et al 2007, cow (May-Panloup et al 2007), pig , and rat (Kameyama et al 2007)). As, at least in the mouse, primordial germ cells in the gonad contain about 2000 copies (Cao et al 2007, Wai et al 2008, it may be estimated that during mammalian oogenesis mtDNA content increases about 100-fold.…”
Section: Introductionmentioning
confidence: 99%
“…Gametes of mice were estimated to contain 10-75 and 1.6 Â 10 5 mtDNA molecules per single sperm and oocyte, respectively (Hecht et al, 1984;Shitara et al, 2000;Steuerwald et al, 2000). Human sperm were estimated to contain 1.4-6.8 molecules (MayPanloup et al, 2003;Amaral et al, 2007) and oocytes 1.93-7.95 Â 10 5 mtDNAs (Steuerwald et al, 2000;Reynier et al, 2001;Barritt et al, 2002;Chan et al, 2005;May-Panloup et al, 2005a;Santos et al, 2006). These estimates lead to ratios of 1:5.7 Â 10 5 -1:2.8 Â 10 4 of paternal-to-maternal mtDNA in human and 1:1.6 Â 10 4 -1:2.1 Â 10 3 in mouse zygotes if paternal mtDNA enters the egg upon fertilization.…”
Section: Introductionmentioning
confidence: 99%